Low-power magnetron sputtering deposition of antimonene nanofilms for water splitting reaction - Wang, Xingli (2022)
Antimonene (Sb) is a novel kind of two-dimensional (2D) material that is predicted to be promising for various applications, such as water splitting and semiconductor devices. Several methods have been reported to prepare Sb nanoflakes/nanofilms; however, it is still relatively difficult to prepare Sb nanofilms. In this work, a method of low-power magnetron sputtering deposition was used for the preparation of Sb nanofilms with lateral dimensions on the centimeter scale and controllable film thickness. It was found that the control of the deposition temperature is important for the final crystalline structure of the nanofilms. Furthermore, the application of the nanofilms as a catalyst for water splitting (hydrogen evolution reaction (HER) and oxygen evolution reaction (OER)) was demonstrated.